The representation of ETA in the Spanish press: terrorism on the front page (1973-1998) - Morera Hernández, Coral (Revista General de Información y Documentación, 2021)
This study analyzes the representation of the ETA attacks on the front pages of the leading Spanish press: La Vanguardia, ABC and El País.  The proposal is to identify, through the content analysis of a quantitative and qualitative basis of a large number of attacks, the iconic and semantic discourse carried out by the papers about ETA terrorism. The work gives an account of the attitude of the press to what was the most serious problem of democracy, and opens a line of research on the evolution of the informative treatment of terrorism.
Keywords: press; ETA; frontpage; terrorism